Análise do juiz das garantias diante do inquérito policial no sistema acusatório (Revista Brasileira Multidisciplinar, 2024)
The present study presents the nuances of the institute of the Judge of Guarantees, inserted in the Brazilian Code of Criminal Procedure (CPP) by Law 13.964 of December 2019. To this end, the role exercised by such figure in criminal prosecution in Brazil is presented, especially in the pre-procedural phase. This research allows to analyze the performance of the judge in the light of the Federal Constitution of 1988 and its approach to the inquisitorial system, as it was allowed to the judge of the criminal action to act in a direct way during the Police Investigation. Based on this, an attempt is made to present the Judge of the Guarantees, the solution found to overcome this approximation and guide the construction of a judge who will act in the investigative phase, guarantor of human and fundamental rights. In this way, criminal prosecution is humanized, paying attention to the premises of a procedural system of guarantees. Finally, the difficulties and impasses for its full practical application are presented, besides evaluating its influence on criminal prosecution in Brazil, concluding that the effective application of the Judge of Guarantees can allow the modernization of the criminal investigation, which will serve as an instrument to diminish the inquisitorial culture in the country's legal system, besides contributing to the search for the judge's impartiality.
Keywords: Keywords: judge of guarantees; police investigation; accusatory model.